The evolution of China's mobile telecommunications industry: past, present and future. (5th January 2005) - Yu, Jiang; Tan, Kim Hua
This paper studies the evolutionary direction of the mobile telecommunications industry in China. Different stages of the industry development process with policy intervention and market competition are examined. The interaction of different players like the Chinese government, incumbent operator, and competitive operator within an actor-network is studied. A process-mapping technique is used to visualise the key drivers of the evolution trajectory of this giant industry. In the meantime, an analytic framework is developed. The future road toward 3G network in China is also analysed.